Analysis of an Iron-Copper Alloy by Calibration-Free Laser-Induced Breakdown Spectroscopy (CF-LIBS) and Inductively Coupled Plasma – Mass Spectrometry (ICP-MS). (22nd September 2022) - Ahmed, Nasar; Shahida, Shabnam; Kiani, Saba Mujeed; Razzaq, Muhammad Inzamam; Hameed, Muhammad Usman; Iqbal, S. M. Z.; Abbasi, S. A.; Rafique, Muhammad; Baig, Muhammad Aslam
Abstract: The purpose of the present work was to monitor the reliability of the calibration-free laser-induced breakdown spectroscopy (CF-LIBS) by comparing the results with inductively coupled plasma - mass spectrometry (ICP-MS). For the laser ablation studies, the plasma was generated by a Q-switched Nd: YAG laser, and the emission spectra of the alloy sample were recorded using a set of Avantes spectrometers covering the wavelength region from 250 to 870 nm. Optical emission spectra confirmed that copper and iron are the major constituents while traces of sodium and magnesium were also observed. The Boltzmann plot method was employed to calculate the plasma temperature to be (8400 to 8700) ± 1000 K using the neutral lines of iron and copper. The electron number density was calculated using the Stark broadened line profiles of the neutral copper lines to be (2.2 ± 0.2) × 10 16  cm −3 . The relative compositions of iron and copper were determined to be 23.85 ± 5% and 76 ± 5% using CF-LIBS. To validate the method, the composition of the alloy was also determined using inductively coupled plasma – mass spectrometry (ICP-MS) and the results were excellent agreement with those by CF-LIBS. This study demonstrated that CF-LIBS is a powerful and reliable tool for quality control of alloys.